Enhancement of Natural Gas Sweetening Performance Using Amine-Based Nanofluids - Alkouni Ejlail,; Zakaria Sihaib,; Abdulwahed Shglabow, (African Journal of Advanced Pure and Applied Sciences, 2025)
The Mellitah gas plant in Libya faces persistent operational challenges in its Acid Gas Removal Unit (AGRU), including high energy consumption for solvent regeneration and limited absorption efficiency. Previous optimization studies identified an effective blend of 39 wt% MDEA and 1 wt% DEA as the optimal amine formulation. This study investigates further performance enhancement by converting this hybrid solvent into a nanofluid containing multi-walled carbon nanotubes (MWCNTs) and silicon dioxide (SiO₂) nanoparticles at concentrations between 0.01 and 0.1 wt%. A validated Aspen HYSYS V11 simulation model of the Mellitah AGRU was used to evaluate the impact of these nanoparticles on absorption efficiency and energy requirements. The MWCNT-based nanofluid achieved an 84.9 % CO₂-removal efficiency, compared with 77.7 % for the base case, and reduced reboiler duty by 21.5 % (≈ 4.0×10⁴ kW). The SiO₂-based nanofluid provided 81.8 % removal with 11.8 % energy savings. The performance improvement is attributed to enhanced heat and mass transfer within the nanofluid. These findings highlight the technical feasibility and strong potential of nanofluid-formulated amine solvents for significant energy reduction and process intensification in industrial gas-sweetening systems.